The Influence of Fuel Type on MotorcycleVehicle Exhaust Emission Tests - Hezron Elyakim Potto; Agung Sudarsono; Mulus Harliady Pamungkas; Annisa Bhikuning (Jurnal Polimesin, 2024)
A vehicle engine's performance can be determined through exhaust emission tests. Exhaust emissions contain air pollutants that result from incomplete fuel combustion in the vehicle's combustion chamber. This is usually due to improper oxygen and air mixture conditions. Gasoline (CxHy) burns and reacts with oxygen (O2) to produce carbon dioxide (CO2), water (H2O), as well as non-toxic gases like nitrogen (N2) and water vapor (H2O (g)). However, it also generates toxic gases such as CO, HC, and Nitrogen Oxides (NOx). Motorcycle exhaust emission tests are commonly conducted using a gas analyzer. In this study, a gas analyser was used to measure the amount of CO, CO2, HC, O2, and NOx emitted from motorcycle exhausts. The tests were carried out using the Vario 160 ABS motorcycle with different types of fuel: RON 92 (S), RON 92 (P), RON 90, RON 98, and RON 92 (R). The data was collected at idle, as well as at 1600 rpm, 1800 rpm, and 2000 rpm. Three measurements were taken for each variable, and the average was calculated. The results showed that RON 98 fuel resulted in better combustion compared to RON 90 and RON 92, as indicated by the CO2 content at idle, which was 13.95%. Additionally, when the motorcycle's engine was throttled, RON 98 fuel did not produce any NOx. The study also revealed that RON 92 (S) fuel led to better combustion compared to both of RON 92 (P) and RON 92 (R), as evidenced by the CO content of 0.05%, CO2 content of 13.63%, HC content of 204 ppm, O2 content of 0.03%, and NOx content of 4 ppm at idle.